94.2k views
5 votes
HNO3 + H2SO4 + NO

You now have these half-reaction equations:
3e + HNO3 → NO
S→ H2SO4 + 6e
Which factor will you use for the top equation?
Which factor will you use for the bottom equation?

2 Answers

2 votes

Answer:

2

1

Step-by-step explanation:

User MikhilMC
by
5.1k points
2 votes

Step-by-step explanation:

The two half equations are;

3e + HNO3 → NO

S→ H2SO4 + 6e

When balancing half equations, we have to make sure the number of electrons gained is equal to the number of electrons lost.

Which factor will you use for the top equation?

We multiply by 2 to make the number of electrons = 6e

Which factor will you use for the bottom equation?

We multiply by 1 to make the number of electrons = 6e

User Ohmen
by
5.1k points